AN ANALYSIS OF COMMUNICATIVE LANGUAGE TEACHING IN ESL LEARNING ENVIRONMENTS (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2026)
This article examines Communicative Language Teaching (CLT) as an effective approach in ESL learning environments. The study focuses on the main principles of CLT and how they influence students’ language development. Special attention is given to the role of interaction, learner participation, and real-life communication in improving speaking and listening skills. The findings suggest that CLT creates a more engaging and meaningful learning process for ESL learners.